RECURRENT MALIGNANT PERIPHERAL NERVE SHEATH TUMOR OF THE LEFT FEMUR POST MULTIMODAL THERAPY IN 61 YEARS OLD MALE: A CASE REPORT - Zuvarcan, Diaz Alifarizki; Bryan, Christopher; Marwanta, Sri (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2026)
Background: Malignant peripheral nerve sheath tumors (MPNST) are rare, aggressive soft tissue sarcomas with a high rate of recurrence and metastasis. Sporadic MPNSTs, especially in older adults without neurofibromatosis type 1, present additional diagnostic and therapeutic challenges. Case Presentation: We report a 61-year-old male with a recurrent sporadic MPNST of the left femur. Over six years, he underwent three surgical excisions, radiotherapy, and two lines of chemotherapy. Despite initial partial response, the disease progressed with pulmonary metastases. Histopathology revealed spindle cell sarcoma with lymphovascular and skeletal muscle invasion. Conclusion: This case highlights the difficulty of achieving durable control in recurrent MPNST despite multimodal therapy. It underscores the importance of vigilant follow-up, individualized treatment plans, and supportive care in advanced disease settings.